PELAFALAN BUNYI DALAM METODE HAPALAN AL QUR’AN SANTRI PONDOK PESANTREN BAITUL QURRO WAL HUFFAZH KERONGKONG - Hikmah, Hikmah; Rismarini Nursaly , Baiq; Mohzana, Mohzana (Universitas Hamzanwadi, 2024)
This study aims to determine the implementation and implications of sound pronunciation in memorizing the Qur'an methode of students at the Baitul Qurro' wal Huffazh Kerongkong Islamic boarding school. This type of research is descriptive qualitative. Primary data sources is the results of interview with the head of the Baitul Qurro' wal Huffazh Kerongkong Islamic boarding school, the head of the Tahfizh Institute, the coach, and the students. While secondary data are used consists of a number of books, research results, journals, and other documents. The results showed that the method used in the pronunciation of sounds in memorizing the Qur'an at Baitul Qurro' wal Huffazh Kerongkong Islamic Boarding School is the jibril method. The implementation of the program applied in learning is by (1) depositing every halaqah, (2) tahsin in general (3) and reading tajweed poems (4) students read together led by one student (5) students who are good at reading are directed to guide their other friends. The implication of sound pronunciation in memorizing the Qur'an is that students can memorize faster and more fluently. The data processing and analysis technique in this thesis consists of data reduction, and data presentation. To test the validity of the data, triangulation was used.